Caracterización molecular de poblaciones naturales de trypanosoma cruzi en muestras de pacientes en ensayos clínicos con drogas tripanocidas - Ramírez Gómez, Juan Carlos (2017)
The natural populations of Trypanosoma cruzi, causative agent of Chagas disease, are composed of multiple clones. The role that parasite genetic diversity plays in clinical and therapeutic scenarios remains unclear. Genetic polymorphism of T. cruzi populations was analyzed before and after treatment with different trypanocidal drugs [E1224 (ravuconazol), benznidazol (BZN) y Fexinidazol (FXN)] of chronic patients. A standardized qPCR assay was used as surrogate marker of treatment failure and only patients with positive qPCR results were included. qPCR positive samples from baseline and follow-up were characterized by T. cruzi satellite DNA (SatDNA) sequence analysis and PCR-RFLP of hypervariable regions of kinetoplastid DNA (kDNA). BZN and FXN showed higher trypanocidal effect than E1224. The genetic variability of T. cruzi populations before and after treatment in patients refractory to E1224 was as high as that observed in patients from the Placebo group. Our findings suggest that the genetic composition of T. cruzi bloodstream populations during follow-up reflects the natural fluctuation of multiclonal parasite populations in chronic Chagas disease. This is the first report documenting the molecular characterization of T cruzi populations after treatment and during natural infection of Chagas disease patients.